Public Health Impact of Androgens - Kanayama, Gen (Curr Opin Endocrinol Diabetes Obes, 2018)
PURPOSE OF REVIEW: To summarize recent findings regarding the public health impact of androgen abuse. RECENT FINDINGS: Abuse of androgens (also called “anabolic-androgenic steroids”) has grown into a major worldwide substance abuse problem involving tens of millions of individuals, of whom about 98% are male. Most androgen abusers are still under age 50 today, and thus the long-term effects of these drugs are only beginning to be understood. Recent studies confirm that long-term supraphysiologic androgen exposure produces cardiovascular toxicity, characterized especially by cardiomyopathy and atherosclerotic disease. Withdrawal from androgens after long-term use may produce prolonged and sometimes irreversible hypogonadism in men. Supraphysiologic androgen levels may sometimes cause irritability, aggressiveness, and violence, whereas androgen withdrawal may cause depression. However, these psychiatric effects are idiosyncratic, affecting only a minority of users. Emerging evidence now also suggests that long-term androgen exposure may cause neurotoxicity, raising the possibility that aging androgen abusers may be at increased risk for dementia. Several recent studies have also described androgen-induced hepatotoxicity, nephrotoxicity, and adverse musculoskeletal effects. SUMMARY: Recent studies have demonstrated marked adverse effects of long-term androgen abuse. As increasing numbers of androgen abusers reach middle age, these effects will likely represent an emerging public health problem.